A PERCEPTION ABOUT THE QUALITY OF PUBLIC EDUCATION IN DEFENSE OF THE CIVIC-MILITARY MODEL - Allison Santos, Allison; Sales Barbosa, Claudio; Marcos de Medeiros, José; Maria do Carmo da Silva Lira, Cícera; Pontual Brotherhood Araujo, Manuela; Sueli Ferreira Silva, Márcia (Revista Gênero e Interdisciplinaridade, 2021)
This study proposes an analysis of the perception of teachers, managers and families about the partnership between military bodies and public schools to improve the quality of basic education in defense of the civic-military model. The objective of this research is to analyze the perception of teachers, managers and families about the contribution of the civic-military educational model to improve the quality of basic education, with an emphasis on access, permanence and learning. The methodology applied was a basic research, with a qualitative and quantitative approach, exploratory, descriptive and field. The sample consisted of 13 managers, 30 elementary and high school teachers, and 21 parents from a city in the metropolitan region of Recife/PE, who were submitted to answer an electronic questionnaire. It was found in this study that managers, teachers and parents agree that the civic-military educational model contributes to improving the behavior of students in the family, school and social environment, they agree that the partnership of Organs military bodies with the public school contributes to improving the quality of basic education with emphasis on access, permanence and learning, and face the partnership with positivity and credibility, especially when it comes to the safety of the school community, indiscipline, fighting drugs and reducing violence. It is concluded that the civic-military educational model can promote moral, civic values, can improve student performance and improve the quality of basic education in public schools.